Choice of Health Options In prevention of Cardiovascular Events for people with Atrial Fibrillation (CHOICE-AF): A pilot study. (1st February 2016) - Lowres, Nicole; Redfern, Julie; Freedman, S Ben; Orchard, Jessica; Bennett, Alexandra A; Briffa, Tom; Bauman, Adrian; Neubeck, Lis
Abstract: Background: Atrial fibrillation (AF), the most common cardiac arrhythmia, is associated with high risk of stroke and significant health burden. Recent emerging evidence suggests that modifying risk factor profiles of people with AF may assist to reduce stroke risk and health burden. Aims: The purpose of this study was to test the feasibility of a brief telephone-based program targeted at improving cardiovascular risk, and health-related quality of life (HRQoL) in patients with AF Methods: This was a pilot study of a brief three-month telephone-based intervention for patients with diagnosed AF. During an initial face-to-face consultation participants were assisted to set individualized risk factor reduction goals and a treatment plan. Participants received phone-based follow-up for three months, with final assessment at three months. Results: Nineteen participants with AF were recruited, with age range 35–82 years (mean 65±13 years) and 53% were male. No changes were observed in either body mass index (BMI) or waist circumference measures. Participation was associated with significant improvement in reported symptom severity ( p =0.005). There were non-significant improvements in physical activity, sedentary behavior, HRQoL, anxiety and depression. Conclusions: Participation in the CHOICE-AF pilot study did not improve BMI or waist circumference: however, it was associated with significant improvement in reported symptom severity. Further research is required to determine the most appropriate model of care for addressing risk factor management for people with AF.